Age, Initial Central Retinal Thickness, and OCT Biomarkers Have an Influence on the Outcome of Diabetic Macular Edema Treated With Ranibizumab– Tri-center 12-Month Treat-and-Extend Study - Lai, Chun-Ting; Hsieh, Yi-Ting; Lin, Chun-Ju; Wang, Jia-Kang; Lin, Chih-Ying; Hsia, Ning-Yi; Bair, Henry; Chen, Huan-Sheng; Chiu, Chiung-Yi; Weng, Shao-Wei (Frontiers in Medicine, 2021)
Objective: We report the tri-center 1-year outcomes of a treat-and-extend (T&E) regimen in four-week intervals with ranibizumab for diabetic macular edema (DME). Methods: In this retrospective study, all eyes received 3 monthly loading injections of 0.5 mg ranibizumab, followed by a T&E regimen for DME. Regression models were used to evaluate the associating factors for visual and anatomical outcomes. Results: Ninety one eyes from 64 patients were enrolled. Mean LogMAR best-corrected visual acuity (BCVA) improved from 0.58 at baseline to 0.36 at month 12 and mean central retinal thickness (CRT) decreased from 411 μm at baseline to 290 μm at month 12. Younger age and eyes having thinner baseline CRT, with ellipsoid zone disruption (EZD), and without epiretinal membrane (ERM) were associated with better final CRT. Moreover, eyes with thicker baseline CRT tend to receive more injections. Among the parameters, only having ERM or EZD was associated with significant BCVA recovery. Conclusions: A T&E regimen with ranibizumab by 4-week intervals is effective in improving BCVA and reducing CRT with efficacy notable starting from the third month. Clinical parameters including age, initial CRT, and presence of ERM or EZD significantly influenced therapeutic outcomes. Moreover, the presence of ERM should not preclude DME patients from receiving anti-VEGF therapy. Future studies with larger cohorts are warranted.